Reduced expression of insulin receptors β subunit (IRSВ) in the myometrium of diabetic women – impact on contractility. (7th June 2011) - Heath, A M; Alquahtni, S; Dawood, F; Wray, S
Abstract : Worldwide, a significant number of diabetic pregnancies result in caesarean sections. We have investigated differences in the effects of insulin on myometrial contractility, and alterations in the expression of IRSβ in the myometrium between diabetic and non-diabetics. Methods: The effects of insulin (7 pM–700 nM) on myometrial contractility from consented term diabetic and non-diabetic women were examined. In some experiments intracellular Ca signals were simultaneously measured. Immunohistochemistry was used to examine the expression of IRSβ and quantified by colour based thresholding analysis. Results: Insulin causes a dose dependent decrease in myometrial contractility in myometrium from both diabetic and non-diabetic women, which was mirrored in the underlying calcium transients. In non-diabetics the decrease was significant (p≤0.05) for all at concentrations, where as in diabetics the decrease was only significant at higher concentrations. At the highest concentrations of insulin the decrease in force in non-diabetics was significantly greater than the diabetics (22±11% n=15, 42±10% n=10, respectively) relative to control period. The results of the immunohistochemistry showed a significant reduction in amounts of IRSβ expressed in the myometrium of diabetics compared to non-diabetics (14±2% (n=8), 21±2% (n=8) respectively). Conclusions: The inhibitory effect of insulin on myometrial contractility was reduced in diabetics compared to non-diabetics, which may be due to alterations in expression of IRSβ in the myometrium. The reduction in calcium transients suggests insulin may affect calcium signalling pathways of the myometrium.